RESISTENSI ANTIBIOTIK DAN PERTUMBUHAN STAPHYLOCOCCUS AUREUS PADA MEDIA AGAR DARAH - Aldinova Gondo Ruming Asmoro; Yusuf Eko Nugroho; Akhmad Mubarok (LPPM Universitas Abdurrab, 2024)
A microorganism growth medium is a material containing nutrients that support the growth and development of microorganisms. This nutrient is called the culture medium, and the growth process is known as culture, which can be enriched by the addition of blood. The aim of the researchers was to examine human blood, sheep's blood and cow's blood as growth media for Staphylococcus aureus bacteria. Is there a difference in the resistance test and growth patterns of Staplococcous aureus bacteria in human blood, sheep's blood and cow's blood media. Growth media in human blood, sheep's blood and cow's blood media. Bacterial growth in human blood media with round-shaped colonies, yellowish white with convex elevation, smooth surface, and medium size on cattle blood with a different type of hemolysis with negative results. smooth, and medium sized on sheep blood media with different types of hemolysis with positive results. Bacterial growth on cow blood media bacterial growth on cow blood media colonies are round, yellowish white with convex elevation, smooth surface, and medium sized on cow blood with hemolysis type which is different from a negative result. conclusion is that the Stapylococcus aureus bacteria has the same inhibitory zone in human blood, sheep blood and cow blood media. There is no difference between human blood, sheep blood and cow blood media. The difference in the type of hemolysis in sheep blood is because it has beta hemolysis type and in human blood, and cow's blood has gamma hemolysis.. Key words: Staphylococcous aureus, growth patterns, blood agar media